Primary Mediastinal Choriocarcinoma in an Elderly Patient with Concurrent Goserelin-Treated Prostate Adenocarcinoma. (6th May 2019) - Røge, Rasmus; Simonsen, Carsten; Petersen, Astrid Christine
Abstract : Mediastinal pure choriocarcinomas are exceedingly rare representations of germ cell tumours and are associated with a poor prognosis. To date, fewer than 20 cases have been reported. This current report describes an elderly patient who developed a large rapidly growing mediastinal tumour. Unfortunately, the patient expired before a definitive diagnosis could be reached. An autopsy revealed that the histomorphological features of the tumour showed two distinct tumour cell populations (syncytio- and cytotrophoblasts), and the diagnosis of choriocarcinoma was made. Immunohistochemical analysis showed a characteristic staining pattern in agreement with published studies. Here, we report a case of primary mediastinal choriocarcinoma in an elderly male with concurrent metastasizing prostate adenocarcinoma treated with long-term goserelin deposits, which, as we speculate, could have induced the choriocarcinoma.